Despejo da favela Jardim Maria Virgínia: fotografias, práticas e representações sociais nos momentos de perigo (1999 e 2011/12) - Martins, José Francisco Greco (2015)
The present research problematizes the social practices and representations within the social space of the favela (slum) Jardim Maria Virgínia (JMV) in the years of 1999 and 2011/12. The area is located in the southern outskirts of the city of São Paulo, in the Campo Limpo district. The research was carried out through a qualitative approach. Besides the usual methods, photographic images were used as a research resource. In 1999, local people were facing a threat of eviction, which was photographed by then. At that time, some inhabitants were interviewed. Returning to the slum in 2011/12, it was investigated what had changed and what had remained steady concerning the social practices and representations experimented by the dwellers in 1999. Through an approach based on the presuppositions of the disruption of politics, the thesis development has revealed the settings of contrasts and continuities between the two moments which are distant in time, as well as it has shown an unstable, provisory and unfinished everyday life, characterized by violence, fear and silence, and whose synthesis is inscribed within the logic of incompleteness